THE USE OF ENCANTADO GAME TO DEVELOP STUDENTS’ SPEAKING SKILLS AT MTS SWASTA INSAN CITA - RIZKI FATIHAH, MENTARI (Faculty of Tarbiyah nad Teacher Training, 2022)
The objective of the research was expected to describe the use of Encantado Game in developing students’ speaking skills. The subject of the research were the seventh grade students of MTs Swasta Insan Cita in 2020/2021 academic year. The seventh grade students of MTS Swasta Insan Cita consisted of 38 students. This research applied by Classroom Action Research. The data of the research were qualitative data and quantitative data. The quantitative data were taken from the test (in the form of Pre-Test, Post test 1 and Post test 2) which given in the end of of every cycle. While qualitative data were taken from Interview, Observation sheet, and dairy notes. The objective of the research was to describe the use of encantado game in developing students speaking skills of the seventh grade students of MTs Swasta Insan Cita Medan in academic year 2020/2021. The showed that encantado games can developed students’ speaking skills of the seventh grade. It can be seen from the results of Pre-test, Post Test I and Post Test II. In Pre-test the result showed that the mean score of students speaking skills was 61,07 (the precentage was29 %, and 11 students who got successful), and Post test I can be seen that mean score of students speaking skills was 70,26 (the precentage was 50%, and 19 students who got successful), And the result of Post test II can be seen that mean score of students speaking skills was 70,84 (there was the precentage was 74 % and 28 students who got successful). And then the total number of seventh grade students of MTs Swasta Insan Cita was 38 students. In conclusion, students speaking skills was developed from Pre-test until Post Test II. Than it can indicates that using encantado game can develop students speaking skills.